Alat Bantu Sistem Inferensi Fuzzy Metode Sugeno Orde Satu - Lizda Iswari; Fathul Wahid (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
Sugeno’s Fuzzy Inference System is a toolbox for building fuzzy logic system based on Sugeno’s Method.The main system characteristic is on its flexibility which means system facilitate user to modify the data system(dynamic system), can be used in any kinds of platforms (portability), and also work for multi operating system.For the portability and multiplatform purpose, sytem was created with C programming languange, following theprinciple of ANSI C. There are 4 kinds of variable that should be entered to the system so that it can workproperly, those are: input variable data, input association data, output function data, and rules data. TheSugeno’s characteristic can be seen from the form of output function data as linear equation. The output of thesystem is defuzzification.Keywords: Fuzzy Logic, Fuzzy Inference System, Sugeno’s Method, Defuzzification